Elimination of Antibiotic Resistant Enterobacteriaceae via Combined Application of Direct Electric Current, Alternating Electric Current and 2-Thiocyanomethylthio benzothiazole - (:unkn) unknown (SOC LEATHER TECHNOL CHEMISTS, 2019)
Multidrug-resistant Enterobacteriaceae originating from animals 'intestinal tracts may be found on salted and soaked hides/skins. The presence of proteolytic, lipolytic, multidrug-resistant Enterobacteriaceae on hides/skins and the resulting destructive processes results in economic losses to the leather industry and creates health hazards for workers. To minimise this destructive bacterial presence, the bactericidal effect of combined application of direct or alternating electric current and an antibacterial agent against multidrug-resistant Enterobacteriaceae were examined in this study. Multidrug-resistant Citrobacter freundii, Citrobacter koseri, Enterobacter cloacae, Serratia rubidaea, Serratia marcescens, Serratia plymuthica, Morganella morganii, Proteus mirabilis, Providencia rettgeri, isolated from soaked hides/skins, were used in the present study. Among the test isolates, Proteus mirabilis, Serratia marcescens, Serratia plymuthica, Serratia rubidaea, were protease and lipase producer strains. All test isolates were resistant to critically important antimicrobials which are used in both human and veterinary medicine. Bacterial effect of combined application of 508mA/cm(2) direct electric current, 454mA/cm(2) alternating electric current and an antibacterial agent (2(thiocyanomethylthio) benzothiazole) against the mixed culture of these micro-organisms were investigated in nutrient broth containing 3% NaCl. After application of six cycles of the combined electric current treatment against the mixed culture of multidrug-resistant Enterobacteriaceae treated with (2-(thiocyanomethylthio) benzothiazole) was completely killed within five hours. The Log(10) reduction of the mixed culture at the end of the experiment was 7.55. In conclusion, the combined application of direct electric current, alternating electric current and antibacterial agent may be used in soak liquors to eliminate proteolytic, lipolytic, multidrug-resistant Enterobacteriaceae in the leather industry.
Keywords: SALTED CATTLE HIDES; BACTERIA; INACTIVATION; MEAT